An examination of chronic ill-health and lifestyle factors among inmates: searching for the healthy immigrant effect in New South Wales Prisons. Issue 2 (11th September 2019) - Field, Courtney; Zovko, Alyssa; Bowman, Julia
Abstract : Purpose: The purpose of this paper is to compare the rates of chronic health conditions and lifestyle factors between Australian-born and overseas-born inmates and to uncover predictive relationships between lifestyle factors and health outcomes for both groups. Design/methodology/approach: Data are presented from a cross-sectional study based on a sample of inmates from correctional sites in New South Wales (NSW). The inclusion of results here was guided by the literature relating to the healthy immigrant effect. Findings: Results indicate that a higher proportion of Australian-born inmates consumed alcohol at higher levels and were more likely to smoke on a daily or almost daily basis than overseas-born inmates. Australian-born inmates were also more likely than overseas-born inmates to have been diagnosed with cancer, epilepsy or hepatitis C. Physical activity predicted the number of diagnoses for Australian-born inmates while physical activity and smoking frequency predicted the number of diagnoses for overseas-born inmates. Practical implications: Overseas-born inmates make up a considerable portion of the prison population in NSW. A better understanding of those health and lifestyle factors that distinguish them from Australian-born inmates provides important insight regarding health promotion and the planning of service provision for those providing health care in this space. Originality/value: Comparison of the health of immigrant and native-born prison inmates has not been undertaken before and promises to provide important information regarding those factors that distinguish a sizeable minority in the prison population.